Méthodes et outils pour l’analyse des verbalisations : une contribution à l’analyse du modèle de l’interlocuteur dans la description d’itinéraires - Marion Wolff; Willemien Visser (Activités, 2005)
Analysing verbalisations is frequently forsaken by ergonomics due to the fact that valid tools, which would allow satisfactory completion of the analysis, are often lacking. This paper, via a study of route description activity, proposes new tools that can be used for verbalisation analysis. It aims at studying the different ways in which people will describe a route depending on whether their interlocutors are very familiar (K) or unfamiliar (NK) with the environment that the route passes through. A first, manual analysis has shown a differential specification of goals and means in the descriptions for K and NK interlocutors. In order to confirm and refine these results, a Cognitive Discursive Analysis (CDA) was conducted, in association with a Geometric Data Analysis (a Principal Component Analysis, PCA). These two further analysis were not only conform with the results of the manual analysis, however they also provided another significant outcome concerning the discursive style used to describe the routes. The complementary use of CDA and PCA methods in Psychological or Ergonomic research is pertinent, particularly when a more subtle analysis of verbal activities is required.